DOES AN ENERGY INDEPENDENT VILLAGE BE FORMED IN NORTH SUMATRA PROVINCE? CASE STUDY: BULUH AWAR VILLAGE, SIBOLANGIT SUB-DISTRICT, DELI SERDANG DISTRICT - Nobrya Husni (Universitas Lambung Mangkurat, 2018)
The potential of renewable energy in the province of North Sumatra has not given confidence to the provincial government to establish Energy Independent Village (EIV). This paper aims to describe the utilization of renewable energy in the village Buluh Awar who have had success using a water-based renewable energy as a source of electrical energy for 25 (twenty-five) years. The approach in this study is qualitative and uses data collection techniques such as observation and interview. The study was conducted in May 2016 and took place in the Buluh Awar village, Sibolangit sub-district, Deli Serdang District. The village was chosen because it has been using the power source coming from renewables for 25 (twenty-five) years, but has not been designated as EIV. The informants were: the user community; plant manager; headman; Department of Mines and Energy (Distamben) North Sumatra Province; and, Distamben Deli Serdang. Analysis of the factors that play a role in the utilization of renewable energy shows that the North Sumatra Province has the ability to form the EIV. Based on the analysis of the factors that play a role in the utilization of renewable energy, it can be concluded that the village Buluh Awar has the ability to set as DME, if followed by the intervention of the local government by providing technical assistance to improve generating capacity so that it can generate more electric power so that society can do creative activity that can push economic growth at Buluh Awar village.